2000
DOI: 10.1046/j.1365-2230.2000.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of skin cancer education on general practitioners' diagnostic skills

Abstract: Seventeen general practitioners (GPs) were evaluated to assess their ability to recognize malignant, borderline and benign skin lesions before and after a novel, cheap and quick skin cancer educational programme. They were tested without prior warning on two occasions using two sets of 30 clinical slides. Between each test the GPs were given a lecture based on an illustrated booklet of similar lesions. The results showed an improvement in the GPs' diagnostic skills (P < 0.05), but nevertheless a wide variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 8 publications
5
39
0
1
Order By: Relevance
“…Four before-and-after studies used traditional lecture settings, 14,15,29,30 and one used a training session 16 to try to improve knowledge of risk factors and diagnostic ability among participants. None of these studies were rated as good quality.…”
Section: Intervention Typementioning
confidence: 99%
See 1 more Smart Citation
“…Four before-and-after studies used traditional lecture settings, 14,15,29,30 and one used a training session 16 to try to improve knowledge of risk factors and diagnostic ability among participants. None of these studies were rated as good quality.…”
Section: Intervention Typementioning
confidence: 99%
“…Some studies had a high risk of selection bias, [13][14][15][16][17]19,20,22,24,25,27,[29][30][31] with little information given (if any) about whether those who participated were different from those who chose not to take part. Almost all studies reported a follow-up period of less than 1 year; 11,14,[17][18][19]21,23,24,27,28,31,33 several tested participants straight after the intervention; 15,16,29,30 and some did not include or state any follow-up period. 20,22,25,32 Therefore, it cannot be determined whether any of the reported improvements persisted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…675,705 Perceived delays in referral by the GP owing to misdiagnosis caused frustration and enhanced anxiety for those who had had such an experience and raised concern that some GPs may not be adequately educated to diagnose suspected SCC. The ability of GPs to diagnose skin cancer varies widely 706,707 and although several studies have evaluated the impact of educational interventions on improving diagnostic accuracy among primary health-care providers, these tend to be isolated interventions and have generally not been rigorously evaluated. 708 Educational interventions have been found to be of variable effectiveness 706,709 and modifying and maintaining clinical practice in the long term can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of GPs to diagnose skin cancer varies widely 706,707 and although several studies have evaluated the impact of educational interventions on improving diagnostic accuracy among primary health-care providers, these tend to be isolated interventions and have generally not been rigorously evaluated. 708 Educational interventions have been found to be of variable effectiveness 706,709 and modifying and maintaining clinical practice in the long term can be challenging. 710 Studies addressing educational interventions with outcomes that focus on performance changes are therefore required, but are outside the remit of the current study and the RCT we are proposing.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the diagnostic accuracy depends on the clinical experience of the specialist (Morton and Mackie (1998)). In general practice, where such experience is low, diagnostic accuracy is quite bad (Bedlow 1995). In the early stages of the disease, the diagnosis is difficult even for experienced clinicians.…”
Section: Malignant Melanomamentioning
confidence: 99%